Communications to the Editor—Exponential Forecasting: Some New Variations - McCormick, Garth P. (Management Science, 1969)
Exponential forecasting or smoothing models are presented which take into account all combinations of trend and cyclical effects in additive and multiplicative form. Although other authors have hinted that the proposed models existed, no one has ever presented them in comprehensive form. This paper presents the nine possible models in graphical form and summarizes them by one summary formula.